Derrotas da seleção brasileira : futebol e identidade nas crônicas de Tostão - Costa, Felipe Rodrigues da (2009)
This study fits into the theoretical framework that seeks to understand the identity construction processes in football. The identities are continually affirmed in the contested space of social memory, in the different sources of record. The objective of this research is to analyze the process of identity construction of the Brazilian football from speeches and pictures of nationalities present in the discourse of sports chronic journalism. In order to delimit the focus of observation, the study takes Tostão, exfootball player and renowned sports chronicler, and his sports chronics as a source to analyze how this character participates in the construction of social memory and in the identity of the national football. A total of 766 chronic was raised and categorized in 21 categories. From this analysis were selected about 40 chronics. The theme of further approach by the chronicler Tostão is the Brazilian National Team, which was subject of 368 chronics (corresponding to 48,04% of publications between 1998 and 2005), which justifies the choice of this thematic. The reading of this period set, besides the familiarization with the object to be studied, the selection process of the subject to be discussed along the study. It also focuses on elements of the biography of Tostão as a player to understand how this actor negotiates and affirms in the present a identitary ideal for the Brazilian football. By the analysis of the speeches presents in the moments of failure of the Brazilian football, this study seeks to identify the narratives of maintenance of discourse of the “art- football” characteristic of the Brazilian football, and the discursive context made by the chronicler Tostão. Thus, it works the notion of the discursive context and the speech analysis, valuing the constructed signification and interpreting as close as possible from the assigned meaning. I concluded there is an attempt from Tostão to gain the recognition that would be due to him inside the representativeness of the 1970 FIFA World Cup conquest, in Mexico, realizing, in his facts review, the desire to be rethought his place beside players related with the genuine Brazilian football.